Fundamentals of management : - Robbins, Stephen P. (Prentice-Hall, 1995)
Brief approach to Principles of Management. Streamlined and specialized to allow full coverage in a single term, Fundamentals of Management provides a sound foundation for understanding key management issues, maintains a functional focus and reaches the latest research studies in the field.